The relevance of geriatric assessments on the association between chronic kidney disease stages and mortality among older people: a secondary analysis of a multicentre cohort study. (23rd July 2022) - Corsonello, Andrea; Soraci, Luca; Ärnlöv, Johan; Carlsson, Axel C; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Mattace-Raso, Francesco; Tap, Lisanne; Formiga, Francesc; Moreno-González, Rafael; Kostka, Tomasz; Guligowska, Agnieszka; et al.
Abstract: Background: age-adapted definition of chronic kidney disease (CKD) does not take individual risk factors into account. We aimed at investigating whether functional impairments influence CKD stage at which mortality increases among older people. Methods: our series consisted of 2, 372 outpatients aged 75 years or more enrolled in a multicentre international prospective cohort study. The study outcome was 24-month mortality. Kidney function was assessed by estimated glomerular filtration rate (eGFR) and albumin-to-creatinine ratio (ACR). Geriatric assessments included handgrip strength, short physical performance battery (SPPB), cognitive impairment, dependency in basic activities of daily living (BADL) and risk of malnutrition. Analysis was carried out by Cox regression, before and after stratification by individual functional impairments. Survival trees including kidney function and functional impairments were also investigated, and their predictivity assessed by C-index. Results: overall, mortality was found to increase starting from eGFR = 30–44.9 ml/min/1.73 m 2 (hazard ratio [HR] = 3.28, 95% confidence interval [CI] = 1.81–5.95) to ACR = 30–300 mg/g (HR = 1.96, 95%CI = 1.23–3.10). However, in survival trees, an increased risk of mortality was observed among patients with impaired handgrip and eGFR = 45–59.9 ml/min/1.73 m 2, as well as patients with ACR < 30 mg/g and impaired handgrip and SPPB. Survival tree leaf node membership had greater predictive accuracy (C-index = 0.81, 95%CI = 0.78–0.84 for the eGFR survival tree and C-index = 0.77, 95%CI = 0.71–0.81 for the ACR survival tree) in comparison with that of individual measures of kidney function. Conclusions: physical performance helps to identify a proportion of patients at an increased risk of mortality despite a mild–moderate impairment in kidney function and improves predictive accuracy of individual measures of kidney function.